Improving Employee Performance: Encouraging Work Motivation, Organizational Culture, and Work Discipline among Employees of PT Siraj Badawi Cukup Rupiah (SBCR) - Azhar Syhatna, Abiyyu; Ryan Syah; Noveria Susijawati (Indonesian Journal of Business Analytics, 2025)
This study analyzes the influence of work motivation, organizational culture, and work discipline on employee performance at PT Siraj Badawi Cukup Rupiah (SBCR). Data analysis was done statistically using a quantitative methodology and a causal associative design. The findings indicate that organisational culture has a beneficial impact whereas work motivation has no discernible effect. Work discipline is the most powerful factor in improving employee performance. These findings suggest that the company strengthen organizational culture, improve motivational programs, and optimize work discipline through supervision and rewards. Integration of these three factors in HR management is important for sustainable employee performance improvement at PT SBCR.